KULTUR MADRASAH ALIYAH PONDOK PESANTREN SABILUL HASANAH BANYUASIN - Munir Mungin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2016)
Indonesia is known in some models of madrasah education. At least, there are four models of madrasah in Indonesia, namely: diniyah madrasah, public madrasah, madrassa special program, and madrasah schools. Model madrasah This latter is a new phenomenon in the history of Islamic education in Indonesia. As in Madrasah Aliyah boarding school Sabilul Hasanah, the education model is trying to combine modern education system but still maintain a traditional pesantren education system. Merging two models of Islamic education system is dimaksudakan for harmony between faith and piety on the one hand and modern science on the other side. The balance of science considered essential to prepare generations of Islam competitive in his day. Keywords: -pendidikan Islam, -madrasah pondok pesantren, -Sabilul Hasanah